2020 vision - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The globalization of science: the place of agricultural research edited by Christian Bonte-Friedheim and Kathleen Sheridan 1996 154pp ISBN 92 9118 029 7